2021
DOI: 10.3390/en14248437
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and Constraints of Sustainable Marketing Mix Development for Poland’s High-Energy Consumer Goods

Abstract: The research examined awareness, prospects and constraints of sustainable marketing mix development (SMD) from the perspective of Poland’s high-energy consumer goods (HECG), i.e., confectionery products, as an example of the Polish food industry. A questionnaire survey was designed for this purpose. The purpose of the survey questions was to evaluate selected areas of SMD; thus, a reference value ratio was proposed. An original approach to pairwise comparisons technique was applied to rank the value of each su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The questionnaire comprised of 40 questions spread within 8 sections. Questions were established on the basis of formerly published surveys with questions successfully applied to similar research studies, see, e.g., [35,37]. The focus of the questions was on eight fundamental aspects of the sustainable marketing mix concept: the awareness among participants related to the sustainable development concept, the productional activity of the surveyed enterprises in relation to the environment, the production activity of the examined companies in relation to social concerns from the perspective of consumers, the production activity of the studied firms in relation to social concerns from the perspective of employees, the incorporation of social and environmental costs within the sustainable pricing of fruit and vegetable products, the evaluation of the sustainable distribution activity of the examined enterprises, the examination of the promotional activity of the surveyed firms in relation to the sustainable development concept and the examination of the development perspectives of sustainable marketing mix for fruit and vegetable products.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire comprised of 40 questions spread within 8 sections. Questions were established on the basis of formerly published surveys with questions successfully applied to similar research studies, see, e.g., [35,37]. The focus of the questions was on eight fundamental aspects of the sustainable marketing mix concept: the awareness among participants related to the sustainable development concept, the productional activity of the surveyed enterprises in relation to the environment, the production activity of the examined companies in relation to social concerns from the perspective of consumers, the production activity of the studied firms in relation to social concerns from the perspective of employees, the incorporation of social and environmental costs within the sustainable pricing of fruit and vegetable products, the evaluation of the sustainable distribution activity of the examined enterprises, the examination of the promotional activity of the surveyed firms in relation to the sustainable development concept and the examination of the development perspectives of sustainable marketing mix for fruit and vegetable products.…”
Section: Methodsmentioning
confidence: 99%
“…By subjecting the cited publications to theoretical analysis, one can conclude that they contain rather selective content devoted to sustainable marketing mix, focusing rather on a broad discussion of the concept of sustainable marketing. Conducting further analysis of the literature in the subject area, publications that focus on the instruments of sustainable marketing mix should be indicated [35][36][37]. The authors present the content in relation to each of the four instruments of the marketing mix-product, price, distribution and promotion mix.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in oil prices negatively affect the economic situation of individual countries, including Poland. In order to cope with the existing social challenges, more attention needs to be paid to sustainable development (Trojanowski, Kazibudzki, 2021). Unfortunately, the BRISC summit 5 that took place in June 2022 indicated that Europe may have major problems related to rising inflation, which can currently be seen in Poland.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They are mainly applied when scaling is very uncertain, but comparing the objects to the others can guarantee more reliable statistical data. The area of the possible applications is extremely large, and some examples are the followings: education [1,2], sports [3][4][5], information retrieval [6], energy supply [7], financial sector [8], management [9], and food industry [10].…”
Section: Introductionmentioning
confidence: 99%